Pengujian Performa Dan Tingkat Stress Pada Website Heymale.Id Menggunakan Autosaved Software Testing GTmetrix dan K6 - Khoirul Anam; Faris Abdillah Haq; Sylvia Fajrin; Fida Rezaldi Rifai (Jurnal Sistem Informasi dan Teknologi Informasi, 2022)
Technological advances have had a huge impact on people's culture because those who used to shop through the market can now easily shop online without having to work hard. Many personal platforms offer their wares or products, one of which is the heymale.id website which is engaged in the online clothing business and is promoted through social media Instagram. As a well-known brand in Indonesia, heymale.id must of course be equipped with adequate performance to avoid overload and lag. Therefore, it is necessary to test website performance using GTmetrix and K6 which are available online. the results of the performance test itself, it was found that this website itself has a grade E (poor) and the results of the web vitals analysis are also below the standard (GTmetrix). The total required to process the performance matrix above so that the website can run shows results at 15.8s.